2008
DOI: 10.1016/j.immuni.2008.05.019
|View full text |Cite|
|
Sign up to set email alerts
|

Gr1+ Inflammatory Monocytes Are Required for Mucosal Resistance to the Pathogen Toxoplasma gondii

Abstract: Summary The enteric pathogen Toxoplasma gondii is controlled by a vigorous innate Th1 response in the murine model. We demonstrate that following oral infection the parasite rapidly recruits inflammatory monocytes (Gr1+ Ly6C+ Ly6G− F4/80+ CD11b+ CD11c−), which establish a vital defensive perimeter within the villi of the ileum in the small intestine. Knock out mice lacking the chemokine receptor CCR2 or the ligand MCP-1, failed to recruit Gr1+ (Ly6C+) inflammatory monocytes, while dendritic cells and resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
334
2
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(369 citation statements)
references
References 46 publications
24
334
2
9
Order By: Relevance
“…Upon closer examination, we discovered that the previous study had used an anti-Gr-1 antibody (clone RB6-8C5) to deplete granulocytes (31). Gr-1 is a shared epitope present on the Ly6C and Ly6G molecules (49), so administration of this antibody would deplete multiple populations of cells expressing Ly6C, including monocytes and macrophages (50), bone marrow cells (51), thymocytes (52), B cells (53), and subsets of T CD8ϩ (54) and T CD4ϩ (52). Our study targeted Ly6G specifically using a different antibody (clone 1A8) that does not recognize significant populations of activated T or B lymphocytes (55).…”
Section: Discussionmentioning
confidence: 99%
“…Upon closer examination, we discovered that the previous study had used an anti-Gr-1 antibody (clone RB6-8C5) to deplete granulocytes (31). Gr-1 is a shared epitope present on the Ly6C and Ly6G molecules (49), so administration of this antibody would deplete multiple populations of cells expressing Ly6C, including monocytes and macrophages (50), bone marrow cells (51), thymocytes (52), B cells (53), and subsets of T CD8ϩ (54) and T CD4ϩ (52). Our study targeted Ly6G specifically using a different antibody (clone 1A8) that does not recognize significant populations of activated T or B lymphocytes (55).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, monocytes may differentiate into anti-inflammatory macrophages (16) or suppress proliferation and production of cytokines by T cells (21), suggesting their role in maintaining homeostasis. In Listeria monocytogenes, Mycobacterium tuberculosis, and Toxoplasma gondii mouse models, for example, monocyte migration from bone marrow results in resistance to infection (15,(22)(23)(24). In contrast, in Trypanosoma brucei and influenza virus models, monocyte recruitment impairs pathogen clearance and exacerbates immunomediated pathology (14,25,26).…”
Section: Importancementioning
confidence: 99%
“…As has been described for infection with several pathogens (9), CCL2 is essential for control of parasite spread and survival of infection in both intraperitoneal (i.p.) and oral Toxoplasma infections (7,8).The strains of Toxoplasma that predominate in Europe and North America, termed types I, II, and III, differ in a wide range of phenotypes, including how they interface with the immune response. The tachyzoite stage of the parasite interacts with the host through secretion of polymorphic proteins from specialized organelles termed rhoptries, which house "ROP" proteins, and dense granules, which contain "GRA" proteins.…”
mentioning
confidence: 99%
“…Although macrophages can themselves be targets of parasite infection, they also can control parasite dissemination through cell-intrinsic, antimicrobial strategies, such as the production of nitric oxide (NO) and reactive oxygen species (ROS) and, in mice, the activation of immunityrelated GTPases (IRGs) (5,6). Recent studies have shown that inflammatory monocytes, in particular, are recruited to the site of infection by the cytokine CCL2 (monocyte chemotactic protein-1 [MCP-1]) (7,8). As has been described for infection with several pathogens (9), CCL2 is essential for control of parasite spread and survival of infection in both intraperitoneal (i.p.)…”
mentioning
confidence: 99%